Roland Barthes’ Semiotics Analysis of Characters From Liyue in The Game Genshin Impact - Ramadany, Ramadany; Hasyim, Muhammad; Sukma, Sukma (Confucius Institute Universitas Sebelas Maret, 2024)
This research aims to find out about the semiotic elements in the characters in the game Genshin Impact as well as the meaning of the semiotic elements in the characters in the game Genshin Impact which have a relationship with culture in China which can be useful in general. The type of research used is qualitative research with descriptive analysis using Roland Barthes' semiotic theory. The techniques used to obtain the results of this research are exploring, searching, writing and collecting data. Based on the results of research and discussion, it shows that, firstly, in the game Genshin Impact, every character from Liyue that is described has semiotic elements that represent the appearance of each character, such as signifiers, signifieds, denotative elements and connotative elements. Second, every character in the game Genshin Impact, especially from Liyue, is explained as having meaning in denotative elements, and connotative elements starting from appearance, clothing and the myth behind each character.